The Effect of Employee Performance Improvement Based on the Influence of Leader-ship on Organizational Culture and Work Motivation through Work Discipline ( Stud-ies on Employees of PT. X Branch of ABC Airport) - Medyana Chandra Kusumasari; Wasi Bagasworo (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2021)
The purpose of this research is to investigate the influence of leadership, organizational culture, work mo-tivation, and work discipline on improving employee performance. The research method used is a surveyed with a causal descriptive analysis technique. Collecting data using the questionnaire method with Likert Scale model, and there are 145 respondents as sample of this research. The analysis technique is using Structural Equation Modeling (SEM). The results of this study indicate that: 1) leadership has a significant effect on organizational culture, 2) organizational culture has a significant effect on work discipline, 3) leadership has a significant effect on job motivation, 4) work motivation has a significant effect on work discipline, 5) work discipline has a significant effect on employee performance, 6) leadership does not sig-nificant influence on employee performance, 7) organizational culture has a significant effect on employee performance through work discipline, and 8) work motivation has a significant effect on employee perfor-mance through work discipline.